SIFAT PAPAN BLOK DENGAN INTI LIMBAH EKSPLOITASI HUTAN LAMPUNG - Suwandi Kliwon; M I Iskandar; Paribotro Sutigno (Jurnal Penelitian Hasil Hutan, 1987)
Blockboards   of six wood species of  logging  waste from  Lampung as core strip material were manufactured in the laboratory, and  their physical  and mechanical properties were tested.The average value of  moisture  content, board density  and strip  density  were 10.09%, 0.63  g/cm3  and 0.49  g/cm3, respectively.  Bending strength parallel to the grain varied between  690.47 kg/cm2  (red meranti)  and 1041.99 kg/cm2 (keruing).  The bending strength  perpendicular   to the grain varied between 112.40 kglcm2 (Bima) and 319.90 kg/cm2 (Pulai), and bending strength parallel to the grain were significantly affected by wood species, but bending strength  perpendicular to the grain  were not.